A Prospective, Monocentric Case-Control Study on Uncontrolled Psoriasis as Independent Risk Factor for a Hypercoagulable State - Tom M. Hillary; Tine Vanhoutvin; Miet Peeters; Maya Imbrechts; Thomas Vanassche; Marjan Garmyn; Séverine Vermeire (Adis, Springer Healthcare, 2024)
Abstract Introduction Chronic inflammatory diseases, including psoriasis, are associated with development of venous thromboembolism (VTE). The clot lysis profile (CLP) provides information on both the clotting tendency and fibrinolysis activity. We hypothesized that CLP in uncontrolled psoriasis patients is disturbed towards more clotting/less lysis compared to healthy controls (HC) and that successful psoriasis treatment could normalize the CLP. In this project, we aim to compare the CLP in patients with uncontrolled psoriasis with age- and sex-matched HC and investigate the effect of anti-inflammatory treatment on CLP. Methods Patients with uncontrolled psoriasis [psoriasis area severity index (PASI) or body surface area (BSA) > 10] (n = 87) and HC (n = 87) were recruited at a tertiary dermatology department. Samples from patients were obtained before treatment and when disease control was obtained (PASI < 3). Amplitude, area under the curve (AUC) and 50% clot lysis time were determined. Results At baseline, psoriasis patients had higher median amplitude and AUC compared with HC (p < 0.0001). After correction for possible confounders (BMI, smoking behavior, psoriatic arthritis, arterial hypertension, diabetes and coronary artery disease), the increased amplitude in psoriasis patients compared to HC remained significant. Successful anti-inflammatory treatment resulted in a significant decrease in amplitude (p = 0.0365). Conclusion This is the first prospective study comparing the CLP of psoriasis patients with that of HC. A significant increase in both amplitude and area under the curve, indicative of a hypercoagulable CLP, was observed in psoriasis patients compared to HC. After successful anti-inflammatory treatment, amplitude significantly decreased.